2016
DOI: 10.3892/etm.2016.3849
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin attenuates hippocampal damage in a rat model of vascular dementia

Abstract: Abstract. Paeoniflorn (PF), the principal bioactive component of Paeoniae radix prescribed in traditional Chinese medicine, possesses a wide range of biological effects and exhibits neuroprotective effects in numerous diseases. Previous studies have demonstrated that PF significantly attenuates memory impairment in rats with vascular dementia (VD). In the present study, a bilateral common carotid artery occlusion (BCCAO) rat model was used to explore the underlying mechanisms of PF. The expression levels of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Several studies have implicated that PF acting through adenosine A 1 receptors decreases infarction caused by acute or chronic cerebral ischemia and alleviates neurobehavioral impairments [ 18 ]. Recent studies have also found that PF can significantly improve cognitive impairments in VD rat models by increasing cerebral blood flow and inhibiting the hippocampal neuronal apoptosis and NF-κB-mediated inflammatory signaling pathway [ 19 , 20 ]. Our previous data also showed that PF could protect hippocampal neurons in rats subjected to cerebral ischemia–reperfusion through activating CB 2 R [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have implicated that PF acting through adenosine A 1 receptors decreases infarction caused by acute or chronic cerebral ischemia and alleviates neurobehavioral impairments [ 18 ]. Recent studies have also found that PF can significantly improve cognitive impairments in VD rat models by increasing cerebral blood flow and inhibiting the hippocampal neuronal apoptosis and NF-κB-mediated inflammatory signaling pathway [ 19 , 20 ]. Our previous data also showed that PF could protect hippocampal neurons in rats subjected to cerebral ischemia–reperfusion through activating CB 2 R [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural compounds emerge as an alternative resource for new antitumor drug discovery, and there is an enhanced interest in seeking new effective agents for the treatment of glioblastoma from natural compounds. PF, as a monomeric natural compound extracted from Radix paeonia Alba , has showed a variety of biological activities such as anti-oxidation, anti-inflammation, neuroprotection, immunoregulation, etc [ 10 , 12 , 13 , 37 ]. In addition, a few studied have been done to investigate anti-cancer activity as well as the underlying mechanisms of PF, which showed that PF could inhibit some tumor types though inducing apoptosis, cell cycle arresting involving multiple signaling molecules like NF-kB, stat3, Notch1 or p53 pathway [ 15 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though a growing number of natural compounds have displayed anti-cancer activities in vitro but among them only a few can play the anti-cancer role in vivo [ 6 , 9 ]. As for PF, previous studies has showed it could be well tolerated in vivo [ 10 , 12 ].Moreover, PF does have the capability to cross the blood–brain barrier. For example, He et al found that PF could quickly penetrate through blood–brain barrier (BBB) to reach hippocampus and maintain a high concentration [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aβ mediated autophagy flux and accumulation of autophagosomes, and the inhibition of autophagy decreased Aβ-induced cytotoxicity after BCCAO injury ( Nagatani et al, 2012 ; Zou et al, 2017 ). Simultaneously, other mechanisms such as apoptosis of hippocampal neurons may be also triggered by the accumulation of Aβ ( Zhang Y. et al, 2016 ; Xiong et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%